Mimesis and imagination from philosophy to literary criticism - Benyoucef, Riadh (Journal of Human Sciences, 2020)
This research seeks to understand the concept of Mimesis in its displacement from the Greek environment to Islamic philosophy, and the confused reception - by Muslim philosophers and critics - of this term associated in its original environment with two literary genres not known by the Arabs, namely tragedy and epic poetry. The gap between Greek poetic theory and the characteristics of Arabic poetry has been an incentive for Muslim philosophers to alter the term with an other: Imagination, which is an authentic Islamic term. But there is a psychological term. Therefore What this study seeks to demonstrate is that both terms are intruders to Arab literary criticism, considering that the Mimesis in its Greek signification is limited to the study of tragical theater and epic poetry, as for the imagination it is a psychological term which renders it ineffective with regard to the aesthetic approach of Arabic poetry.